PERSEPSI MAHASISWA PADA SALAH SATU PERGURUAN TINGGI SWASTA DI BANDUNG TERHADAP BRAND IMAGE BANK BRI - Deselyne Leslie, Lahengky Melinda; Setiawan, M. Lutfi; Kamelia, Kamelia; Hatimatunnisani, Hani; Fauzany, Riffka (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2024)
This study analyzes students' perception of the brand image of Bank Rakyat Indonesia (BRI). Using quantitative methods, data was collected through a questionnaire distributed to 75 students of the Bandung Pajajaran Polytechnic. The results showed that the majority of students had a positive perception of BRI, especially in terms of reputation and product suitability. However, students want improvements in digital services and customer service responsiveness. This research suggests that BRI should focus more on digital innovation and improving customer service to strengthen its brand image among students